2019
DOI: 10.3389/fphys.2019.01385
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Oxygenation During Hypoxic Exercise in Children and Adults

Abstract: IntroductionWhile hypoxia is known to decrease peak oxygen uptake (V.⁢o2 max) and maximal power output in both adults and children its influence on submaximal exercise cardiorespiratory and, especially, muscle oxygenation responses remains unclear.MethodsEight pre-pubertal boys (age = 8 ± 2 years.; body mass (BM) = 29 ± 7 kg) and seven adult males (age = 39 ± 4 years.; BM = 80 ± 8 kg) underwent graded exercise tests in both normoxic (PiO2 = 134 ± 0.4 mmHg) and hypoxic (PiO2 = 105 ± 0.6 mmHg) condition. Continu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 42 publications
4
9
2
Order By: Relevance
“…First, the variability in several outcome measures was relatively high, so similarities between groups may be due to a lack of statistical power in those comparisons. However, our previous work in children cohorts [30,31] suggested that this study was sufficiently powered to detect differences in exercise capacity. Furthermore, participants with BPD were excluded from the study which, while allowing an investigation of prematurity per se, may underestimate the effect of pre-term birth in relation to the entire population.…”
Section: Discussionmentioning
confidence: 92%
“…First, the variability in several outcome measures was relatively high, so similarities between groups may be due to a lack of statistical power in those comparisons. However, our previous work in children cohorts [30,31] suggested that this study was sufficiently powered to detect differences in exercise capacity. Furthermore, participants with BPD were excluded from the study which, while allowing an investigation of prematurity per se, may underestimate the effect of pre-term birth in relation to the entire population.…”
Section: Discussionmentioning
confidence: 92%
“…Endurance exercise under hypoxia decreases skeletal muscle oxygenation, such as decreased oxhb and StO 2 , and increased dxhb compared with that under normoxia. Skeletal muscle oxygenation during endurance exercise under hypoxia can decrease due to increased skeletal muscle extraction and a reduction in oxygen supply to the skeletal muscle tissue compared with that under normoxia [ 11 , 12 , 13 , 28 ]. Therefore, we examined changes in skeletal muscle oxygenation during endurance exercise at the same relative exercise intensity under hypoxia and normoxia.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, exercise under hypoxia has been shown to have some adverse effects on skeletal muscle oxygen profiles [ 10 , 11 , 12 , 13 ]. Acute exposure to hypoxia induces systemic hypoxia, which can compromise skeletal muscle oxygenation and subsequently, skeletal muscle ability [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations